Eco-Friendly Concrete with High Initial Compressive Strength Using Recycled Concrete, Silica Fume and Superplastiser - Yuhanah, Tri; Mayasari, Devita; Iduwin, Tomy (Institute Of Advanced Knowledge and Science, 2025)
The increasing demand for concrete in the construction industry continues to progress every year. Various concrete innovations have been developed to meet the needs of projects that require fast turnaround times and high efficiency but have a negative impact on the environment. Concrete waste as a solution to reduce construction waste, silica fume as a substitute for cement, so that it can reduce the use of natural materials and increase the resistance of concrete to cracks and corrosion, and superplasticizer increases the strength and flow ability of concrete. This research focuses on the use of silica fume and concrete waste as a partial substitution for concrete materials, as well as the use of superplasticizers to increase the compressive strength of concrete. Silica fume is used as a cement substitution with variants of 0%, 5%, 10%, and 15%, concrete waste is used as a substitute for coarse aggregate by 25%, and superplasticizer by 1%. In normal concrete and variants 1 to 4, the compressive strength value at the age of 28 consecutive days is 25,370 MPa; 26,125 MPa; 26,597 MPa; 27,634 MPa; and 29,520 MPa. The tensile strength is 2,025 MPa, 2,122 MPa, 2,146 MPa, 2,334 MPa and 2,594 MPa, respectively. Through this study, the right composition was obtained to make concrete with high initial compressive strength, the percentage increase in high initial compressive strength value at the age of 3 days was 47.110%.